Retiform Purpura After Transcatheter Arterial Chemoembolization: A Case Report. (February 2018) - Hansen, Trevor; Olsen, Keith; White, Kevin; Keller, Jesse
Abstract : Abstract: Cutaneous complications secondary to transcatheter arterial chemoembolization (TACE) are exceptionally rare and may occur because of nontarget embolization of terminal vessels supplying the skin. We present a patient who developed painful retiform purpura on the right flank shortly after TACE for treatment of hepatocellular carcinoma. Biopsy revealed intravascular tan to yellow amorphous spherical structures within the dermis, confirming the presence of foreign material within these vessels. The authors review the literature and discuss previous cases of skin lesions manifesting after TACE, as well as potential factors influencing the probability of cutaneous complications. Histopathologic findings described in similar cases are presented. Prophylactic measures and attempted treatments to reduce likelihood of long-term injury are also reviewed. An awareness that cutaneous injury is a rare, but potential complication of transcatheter arterial embolization, as well as an understanding of management options is important for any provider using this procedure.